2014
DOI: 10.1016/j.jpeds.2014.07.048
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of Oral Contraceptives and Changes in Blood Pressure and Body Mass Index in Healthy Adolescents

Abstract: Objectives To describe changes in systolic blood pressure (SBP), diastolic blood pressure (DBP) and body mass index (BMI) associated with initiation and continued use of combined oral contraceptives (COCs) in healthy adolescents. Study design This observational, matched cohort study was conducted in two large health systems. Utilizing claims and electronic medical records, we identified adolescents 14-17.9 years of age initiating medium-dose COCs (containing 30 or 35 micrograms of ethinyl estradiol or equiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
2
2

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 24 publications
2
23
2
2
Order By: Relevance
“…19 Similar trends were observed for cardiorespiratory fitness in our article, although nonsignificant. Previous studies have demonstrated an association between hormonal contraceptive use and elevated BP, 20 yet recent cross-sectional literature shows that the influence of oral contraceptives in development of BP during adolescence is nonsignificant, 21 in agreement with our results. Further literature supports the detrimental effect of lower SES in childhood on health in adulthood.…”
Section: Discussionsupporting
confidence: 93%
“…19 Similar trends were observed for cardiorespiratory fitness in our article, although nonsignificant. Previous studies have demonstrated an association between hormonal contraceptive use and elevated BP, 20 yet recent cross-sectional literature shows that the influence of oral contraceptives in development of BP during adolescence is nonsignificant, 21 in agreement with our results. Further literature supports the detrimental effect of lower SES in childhood on health in adulthood.…”
Section: Discussionsupporting
confidence: 93%
“…Our search returned 542 unique articles/abstracts, among which nine journal articles and six abstracts were selected. Most of the articles were excluded because they did not investigate drug effectiveness or safety ( n = 350), some for using only EHR ( n = 47) or claims data ( n = 10), some for using both types of datasets without data linkage ( n = 55).…”
Section: Existing Literature On Linking Ehr To Claims Data To Study Dmentioning
confidence: 99%
“…One matched cohort study published since this review found no significant changes in blood pressure among adolescents using COC during 18 months of follow-up when compared with controls 369. No studies were identified that examined changes in blood pressure with time among patch users.…”
Section: What Follow-up Is Required For Women Continuing With Usementioning
confidence: 88%
“…In one matched cohort study of adolescents using COC published since this review,369 BMI increased by a mean of 0.04 kg/m 2 per month among COC users versus 0.025 kg/m 2 per month among controls. If BMI is ≥35 kg/m 2 at follow-up, women should be advised to switch to an alternative method of contraception.…”
Section: What Follow-up Is Required For Women Continuing With Usementioning
confidence: 95%